The Effect of Gratitude Intervention on Adolescents' Subjective Well-Being - Yulius Sodah (Journal of Social Research, 2026)
Adolescents’ subjective well-being has become a significant global concern due to increasing psychological stress, academic pressure, and emotional instability during developmental transitions. This study aims to examine the effect of a gratitude intervention, specifically gratitude letter writing, on adolescents’ subjective well-being. The research employed a quantitative experimental design involving high school students aged 15–16 years who were divided into experimental and control groups. The experimental group participated in a structured gratitude letter-writing activity for five consecutive days, while the control group did not receive any intervention. Data were collected using the **Satisfaction with Life Scale (SWLS)**, the **Multidimensional Students’ Life Satisfaction Scale (MSLSS)**, and the **Positive and Negative Affect Schedule—Expanded Form (PANAS-X)**, as well as the **Gratitude, Resentment, and Appreciation Test (GRAT)**. The results of independent-samples t-tests and paired-samples t-tests showed that adolescents in the experimental group experienced a significant increase in life satisfaction and positive affect compared to the control group. Although negative affect decreased in the experimental group, the difference between groups was not statistically significant. The discussion confirms that gratitude interventions effectively enhance positive psychological states among adolescents. In conclusion, gratitude letter writing is a simple and effective intervention to improve adolescents’ subjective well-being, particularly in strengthening life satisfaction and positive emotions, while its effect on reducing negative affect remains limited.